Termites live in a material world: exploration of their ability to differentiate between food sources - Inta, Ra (The Royal Society, 2007)
Drywood termites are able to assess wood size using vibratory signals, although the exact mechanism behind this assessment ability is not known. Important vibratory characteristics such as the modal frequencies of a wooden block depend on its geometry and boundary conditions; however, they are also dependent on the material characteristics of the block, such as mass, density and internal damping. We report here on choice experiments that tested the ability of the drywood termite Cryptotermes secundus to assess wooden block size using a solid wooden block paired with a composite block, the latter made of either wood and aluminium or wood and rubber. Each composite block was constructed to match mass or low-frequency vibratory modes (i.e. fundamental frequency) of the solid wooden block. The termites always chose the blocks with more wood; they moved to the solid wooden blocks usually within a day and then tunnelled further into the solid wooden block by the end of the experiment. Termites offered composite blocks of wood and rubber matched for mass were the slowest to show a preference for the solid wooden block and this preference was the least definitive of any treatment, which indicated that mass and/or damping may play a role in food assessment. This result clearly shows that the termites were not fooled by composite blocks matched for mass or frequency, which implies that they probably employ more than a single simple measure in their food assessment strategy. This implies a degree of sophistication in their ability to assess their environment hitherto unknown. The potential importance of alternative features in the vibrational signals is discussed.